E <--|--> F --> G --> H
I understand why F --> H and G some
spets wrote:Hi, I'm working on PS's section on formal logic and there is one problem that I don't quite understand:
E <--|--> F --> G --> H
I understand why F --> H and G someEare inferences, but the answer key also includes H someE. I'm not sure how this inference can be made since it shouldn't be able to go against the arrow, even with the inherent inference (H some G).
Knockglock wrote:spets wrote:Hi, I'm working on PS's section on formal logic and there is one problem that I don't quite understand:
E <--|--> F --> G --> H
I understand why F --> H and G someEare inferences, but the answer key also includes H someE. I'm not sure how this inference can be made since it shouldn't be able to go against the arrow, even with the inherent inference (H some G).
You have to combine inferences, I think. I'm a bit rusty at this, but let me give it a shit.
F--->H (All F's are H)
+
F<--/-->E (No F's are E)
= (well if All F's are H, and No F's are E, some H's can't be E's)
H <some / > E (some H's can't be E's)
Apologies if this is incorrect, like I said i'm super rusty and am in need of a formal logic review.
Return to â€œLSAT Prep and Discussion Forumâ€?
Users browsing this forum: PrezRand and 13 guests